Osimertinib Rechallenge With Bevacizumab vs. Chemotherapy Plus Bevacizumab in EGFR-Mutant NSCLC Patients With Osimertinib Resistance - Cui, Qingli; Hu, Yanhui; Cui, Qingan; Wu, Daoyuan; Mao, Yuefeng; Ma, Dongyang; Liu, Huaimin (Frontiers in Pharmacology, 2022)
At present, treatment options for osimertinib resistance are very limited. Dual inhibition of vascular endothelial growth factor (VEGF) and epidermal growth factor receptor (EGFR) significantly improved the progression-free survival (PFS) of advanced EGFR-mutant non-small cell lung cancer (NSCLC). After EGFR-tyrosine kinase inhibitor (TKI) resistance, EGFR-TKI continuation combined with VEGF inhibitors still has clinical benefits. It is unclear whether the addition of bevacizumab after osimertinib progresses will prolong the duration of osimertinib benefit. We screened 1289 patients with NSCLC and finally included 96 patients to evaluate osimertinib combined with bevacizumab (osi+bev) versus chemotherapy combined with bevacizumab (che+bev) for the patients with acquired resistance to osimertinib. The overall response rate (ORR) for osi+bev and chem+bev were 15.8% (6 of 38) and 20.7% (12 of 58), respectively. The median PFS for osi+bev and che+bev were 7.0 and 4.9 months (HR 0.415 95%CI: 0.252-0.687 p=0.001). The median OS for osi+bev and che+bev were 12.6 and 7.1 months (HR 0.430 95%CI: 0.266-0.696 p=0.001). Multivariate analyses showed that without brain metastases and osi+bev treatment after osimertinib resistance correlated with longer PFS (p=0.044, p=0.001,), while the median PFS of osimertinib less than 6 months (p=0.021) has detrimental effect on sequent treatment. Only osi+bev treatment was identified as an independent predictor of OS (p=0.001). The most common adverse events (AEs) grade ≥ 3 were hypertension (13.2%) and diarrhea (10.5%) in osi+bevacizumab group. Neutropenia (24.1%) and thrombocytopenia (19%) are most common AEs grade ≥ 3 in che+bev group. The overall incidence of serious AEs (grade ≥ 3) was significantly higher in chemotherapy plus bevacizumab group. Our study has shown the superiority of osi+bev compared to che+bev after failure of osimertinib, making it a preferred option for patients with acquired resistance to osimertinib.